2000
DOI: 10.1097/00003246-200003000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Repeat computed tomographic scan within 24-48 hours of admission in children with moderate and severe head trauma

Abstract: A second routine prescheduled head CT scan within 24-36 hrs after admission in pediatric patients with moderate to severe head trauma is unlikely to yield any change in therapy. Clinically and intracranial pressure-oriented CT scan may better select and diagnose patients who require changes in therapy, including surgery. Studies aimed to determine the ideal timing for the second are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 16 publications
8
65
2
2
Order By: Relevance
“…In pediatric guidelines and retrospective pediatric studies of all traumatic brain injuries, repeat imaging is recommended for some observed patients given concern for progression of injury [8,16,24,25,26,27]. While repeat imaging was common in our study population, the initial repeat CT image showed an increase in hematoma size in a minority of patients and led to surgery in only 1 patient.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In pediatric guidelines and retrospective pediatric studies of all traumatic brain injuries, repeat imaging is recommended for some observed patients given concern for progression of injury [8,16,24,25,26,27]. While repeat imaging was common in our study population, the initial repeat CT image showed an increase in hematoma size in a minority of patients and led to surgery in only 1 patient.…”
Section: Discussionmentioning
confidence: 92%
“…While repeat imaging was common in our study population, the initial repeat CT image showed an increase in hematoma size in a minority of patients and led to surgery in only 1 patient. Two smaller studies by Durham et al [24] and Tabori et al [27 ]noted that management was affected by an initial repeat CT in only a small minority of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial pressure (ICP) monitoring plays a valuable role in the management of children with head injuries as well as atraumatic conditions associated with intracranial hypertension [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14]. Overall, insertion of an ICP monitor is felt to be a safe and effective adjunct in the management of raised ICP, with a low incidence of hemorrhagic or infectious complications [15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…However, increased awareness of the risks of HCT and the lack of evidence supporting its use suggest that routine follow-up HCT may not be justified in this patient population. In fact, numerous studies do not support routine repeat HCT without changes in clinical exam or neurological deterioration [5,6,7,8,9,10,11,12,13,14,15]. However, most of these studies were conducted in adults; it is unclear if these findings can be extrapolated to children.…”
Section: Discussionmentioning
confidence: 99%